Irradiation protocol for cultural heritage conservation treatment - Maria Luiza Emi Nagai; Paulo de Souza Santos; Pablo Antonio Vasquez Salvador (Brazilian Journal of Radiation Sciences)
Ionizing radiation supplied by cobalt-60 is an excellent alternative tool to the traditional process of decontamination of cultural and historical materials, mainly because of its biocidal action. Analyzing the occurrence of requests for treatment materials from cultural institutions with ionizing radiation for fungal decontamination in the Multipurpose Gamma Irradiation Facility of the Nuclear and Energy Research Institute - CTR/IPEN, there was a need to establish a protocol for the care of institutions and individuals carrying cultural and historical collections. The study proposal was the establishment an efficient and reproducible model of an irradiation protocol for the treatment of cultural heritage materials in industrial irradiators, respecting the ethical principles of conservation and restoration activities. The objective of the protocol is to be a practical guide, from the detection of the problem to the final cleaning, so that conservator-restorers and professionals of the irradiation can act in a collaborative and objective way to reach the objective of the treatment.